Uji Zona Hambat Kombinasi Ekstrak Bawang Putih (Allium sativum) dan Buah Mengkudu (Morinda citrifolia) terhadap Bakteri Escherichia coli - R Abyseka Prayogo; Dorta Simamora (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Escherichia coli bacteria is the most common cause of gastroenteritis (diarrhea), urinary tract infections (UTI), food poisoning, and other clinical problems such as neonatal miningitis. Garlic (Allium sativum) and Noni fruit (Morinda citrifolia) are plants that have antimicrobial properties, which can be used against bacteria such as E. Coli. This study was conducted to determine the inhibition zone combination of garlic extract (Allium sativum) and Noni fruit (Morinda citrifolia) against gram negative bacteria E. Coli. The research was conducted at the Laboratory of Microbiology at the Faculty of Medicine, University of Wijaya Kusuma Surabaya, and has been ethically feasible. This study was divided into 4 groups with replications 6 times each; group P0 (sterile distilled water), P1 (50% garlic + 25% noni fruit), P2 (50% garlic + 50% noni fruit), P3 (50% garlic + 75% noni fruit). Data were analyzed using One-way ANOVA test. The analysis results showed that the average diameter of the inhibition zone formed was the largest in group P1 (10.7 mm) and the smallest in group P0 (0 mm), while in P2 (9.89 mm), and P3 (9.77 mm). Based on the analysis test, the higher the concentration of noni fruit given to the extract combination resulted in the smaller diameter of the inhibition zone. This occurs due to the combination of garlic and Noni fruit has an antagonistic effect that depend on bacterial species, temperature, pH, chemical structure, chemical reactions, and concentrations or doses of antimicrobial compounds. The results also showed that there was no significant difference between group P1 and group P2, group P1 with group P3 and group P2 with group P3 showing p-value> 0.005.